Participação social e políticas sociais : o trabalho desenvolvido pelo Programa Morar Legal da Secretaria Municipal de Habitação do Município do Rio de Janeiro - Ferreira, Roberta Oliveira (2005)
The program Morar Legal serves the Irregular and Clandestine Places of the city of Rio de Janeiro, that can be considered informal areas of the city, because there is not infrastructure in these places and the land is ilegal. illegal for the reason of the urbanistic laws had been broken. This paper aims at evaluating the work developed by the program Morar Legal of the Habitational Secretary of Municipality of Rio de Janeiro, which focus the work with popular participation by the citizen users of this social policy developed by the program.